Autoimmune encephalitis followed by hemophagocytic lymph histiocytosis: a case report - Huang, Li; Tan, Jie; Lin, Peihao; Chen, Zixuan; Huang, Qihua; Yao, Haiyan; Jiang, Lihong; Long, Baoyi; Long, Youming (Frontiers in Immunology, 2024)
Objective: To report three cases of autoimmune encephalitis followed by hemophagocytic lymphohistiocytosis. Methods: Data of relevant patients treated between 2019 and 2022 were retrospectively collected from the Department of Neurology at the Second Affiliated Hospital of Guangzhou Medical University. Results: The age at onset of the three collected patients were 37, 63, and 36 years. All three patients were female and presented with cognitive dysfunction and seizures. Behavioral and psychological symptoms were also observed in 2 cases. All patients were positive for autoantibodies in both the cerebrospinal fluid and serum, while two showed multiple abnormal brain signals on magnetic resonance imaging. All patients exhibited hypocytosis and elevated soluble CD25 and serum ferritin levels. The final diagnoses in two cases were lymphomas, while the remaining case without tumors suffered from a severe infection. All patients received immunotherapy, and the two with lymphoma received anti-tumor treatment. The patient with infection died, and two patients with tumors improved after chemotherapy. Conclusion: Autoimmune encephalitis followed by hemophagocytic lymphohistiocytosis is a rare and severe condition. Prompt attention should be paid to the decline in blood cell counts, particularly in patients who show slight improvement after immunotherapy, or have a risk of lymphoma. Screening for potential tumors, infections, and early treatment may help these patients.